Smokers and non smokers: A comparison of Oral health practices and effect of non-surgical Periodontal Therapy on their Periodontium (2015)
To assess the oral hygiene measures and self-report oral symptoms of smokers and non-smokers, as well as evaluate and compare the effect of non-surgical periodontal therapy on their periodontium. This was a quasi-experimental study conducted on smokers and non-smokers. Adult patient smokers were recruited into the study group and matched with age and sex controls (non-smokers). Data was collected on oral hygiene measures and self-reported oral symptoms. The patients were examined and evaluated using oral indices. Each patient had scaling and root planing done and was re-examined after six weeks. Data was analysed using SPSS. Seventy-two patients completed the study with age ranging from 20 to 65 years and a mean age of 43.7 (± 17.8) years. Twenty-one percent (21%) of smokers and 42% of the non-smokers reported experiencing gum bleeding, p =0.041. Sixty percent of the smokers reported stains on their teeth compared to 29.7% of non smokers, p = 0.028. The baseline gingival and calculus indices were lower in smokers compared to non smokers while the plaque index was higher among the smokers. The response to scaling and root planing was worse among smokers comparing their gingival and calculus indices but better in terms of the plaque indices, however, these were not statistically significant. There were no significant differences between the response of smokers and non smokers to non surgical periodontal therapy although smokers experienced gingival bleeding less often and have lower gingival index